Motivation and Halal Tourism: Middle-class Tourist Perspective to Beach Club - Putri, Trinitaria Marlis; Riyantori, Refki (ILTIZAM Journal of Shariah Economics Research, 2024)
As the capital city of West Sumatra, Padang only has a few tourist destinations. Domestic tourists choose to go to other cities, such as Bukittinggi, Payakumbuh, and Solok, while international tourists go to Mentawai Island. Marawa Beach Club Padang (MBC), hopefully, could be one of the tourist attractions that is available in Padang. This beach club offers both natural and human-made spots. This research was designed to investigate what are the tourist's motivation to go to a beach club. Further, since the majority of Padang citizen are Muslim, this research will explore their understanding of halal tourism that has been implemented in MBC. This research was conducted as a qualitative approach research which deep observation and structured interviews were done with 25 informants. The informants were the tourists we found in the club whom we classified the middle-class tourists since the beach club offers quite high standards of price. The results show that tourists got motivated to go because of the view the club offers, and the vibes to chill, relax, and enjoy food while the understanding of halal tourism is still very low.